Spillover effects of mandatory portfolio disclosures on corporate investment - Sani, Jalal; Shroff, Nemit; White, Hal (Journal of Accounting and Economics, 2023)
This paper examines whether portfolio disclosure requirements for actively managed investment funds affect the investment decisions of the firms they own. We argue that mandatory portfolio disclosures reduce fund managers' incentive to collect and trade on private information, which reduces the stock price informativeness of their portfolio, and thus portfolio firm managers' ability to learn from their firms' stock prices. Using a difference-in-differences design around the May 2004 SEC regulation requiring more frequent fund disclosure, we find that investment sensitivity to stock price declines for firms with significant ownership held by actively managed funds affected by the regulation. The decline in investment-price sensitivity is concentrated among firms that are (i) owned by funds with larger expected proprietary costs and (ii) more likely to learn from price. Our results suggest that portfolio disclosure requirements have spillover effects on corporate investment by curtailing managers’ opportunities to learn from price.